2012
DOI: 10.7314/apjcp.2012.13.9.4445
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Invasive Breast Ductal Carcinoma, NOS, Diagnosed in a Tertiary Institution in the East Coast of Malaysia with a Focus on Tumor Angiogenesis

Abstract: Background: Prognosis of breast cancer depends on classic pathological factors and also tumor angiogenesis. This study aimed to evaluate the clinicopathological factors of breast cancer in a tertiary centre with a focus on the relationship between tumor angiogenesis and clinicopathological factors. Methods: Clinicopathological data were retrieved from the archived formal pathology reports for surgical specimens diagnosed as invasive ductal carcinoma, NOS. Microvessels were immunohistochemically stained with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…Therefore, an increase in the number of capillaries indicates an increased probability of invasion and metastasis (2). Ch'ng et al (14) analyzed CD34 expression in 94 invasive ductal breast cancer tissue samples and identified that CD34 was highly expressed in the youth group (aged ≤55 years), but was not associated with other clinicopathological factors. In addition, the clinical stage of breast cancer was determined to be a major contributor to a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, an increase in the number of capillaries indicates an increased probability of invasion and metastasis (2). Ch'ng et al (14) analyzed CD34 expression in 94 invasive ductal breast cancer tissue samples and identified that CD34 was highly expressed in the youth group (aged ≤55 years), but was not associated with other clinicopathological factors. In addition, the clinical stage of breast cancer was determined to be a major contributor to a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…According to a study with angiogenesis, majority of the breast cancer patients had advanced stage disease with poorer prognostic factors as compared to other local and western studies. Breast cancer in younger patients might be more proangiogenic (Ch'ng et al, 2012).…”
Section: Targeting Vegfmentioning
confidence: 99%